The socio-cultural study of folklore - Islam, Mazharul . (Dhaka : Bangla Academy, 2001)
With reference to Bangladesh.
Bibliography : p. 295-304.
Includes some passages in Bengali.
Keywords: Folklore -- Bangladesh